Retrospective electron microscopy: preservation of fine structure by freezing and aldehyde fixation - Fortunato, Franco; Hackert, Thilo; Büchler, Markus W.; Kroemer, Guido (Molecular & cellular oncology, 2016)
For many years it has been believed that ultrastructural analysis by transmission electron microscopy (TEM) is not possible using frozen tissues. We have developed a TEM method that allows the evaluation of organelles using pancreatic tissue that was previously liquid nitrogen snap-frozen and stored long-term at −80°C. This method is suitable for the quantitative assessment of mitochondria, rough endoplasmic reticulum (RER), and Golgi structures, as well as organelles originating from autophagy signaling. Frozen pancreatic tissue exhibited no signs of freezing- or storage-related damage and was undistinguishable from fresh material subjected to standard glutaraldehyde fixation. Since pancreatic tissue is the most delicate tissue to work with due to the high expression of digestive enzymes, our method is also suitable for other tissue types such as liver. Thus, by applying proper tissue freezing and fixation techniques, retrospective TEM analysis can be performed on mammalian tissues in a time- and cost-saving manner.